CODEGER-UWE - Model Driven Web Application Development Tool - Tran, Dinh Dien; Huynh, Quyet Thang; Bui, Thi Mai Anh; Hoang, Thanh Dat; Nguyen, Phi Le (JST: Engineering And Technology For Sustainable Development, 2021)
In this paper, we present a CODEGER-UWE tool tool to support model-driven web application development. The CODEGER-UWE tool has integrated rule for transformation Model and code generation rules to create web applications for the JSF platform automatically. CODEGER-UWE implemented as a plugin for the MagicDraw tool which allows the generation of source code from UWE models that correspond to the components of the MVC model. This is a tool with a clear, handy development process, applying tools to develop web applications will greatly reduce the time for developing Web applications.